The role of technology orientation and big data analytics (BDA) adoption on the business performance among Malaysian SMEs: Mediating role of competitive advantage - Seow, Lai Yeow (2023)
The emergence of big data has revolutionized the way companies operate and make decisions. Big data refers to the large and complex data sets that are generated from various sources, including social media, customer interactions, and website. However, for SMEs in developing countries, such as in Malaysia, leveraging big data can be a daunting task. SMEs face several challenges in analysing big data, including lack of technical expertise, limited resources, and inadequate infrastructure. As a result, SMEs may not be able to fully realize the potential benefits of big data, including enhanced business performance and competitive advantage. Thus, this research “The role of technology orientation and big data analytics (BDA) adoption on business performance among Malaysian SMEs: Mediation role of competitive advantage” aims to investigate the role of technology orientation and BDA adoption on business performance among Malaysian SMEs in the service sector, with a focus on the mediating effect of competitive advantage. The objective of this research is to examine the relationship between variables such as technology orientation, big data analytics (BDA) adoption, competitive advantage, and business performance of Malaysian SMEs. The theory applied in this research study is resource-based view (RBV) theory. The RBV theory aims to identify the role of technological resources and capabilities of SMEs on their competitive advantage and business performance. A quantitative research method was used to collect and analyse the data for this research. The key informant was the SMEs business owners and those with high-level management position that are knowledgeable about their company. While the unit of analysis is on the companies in which the respondents are representing.